Rola szlaku CD40/CD40L w biologicznej aktywności płytek krwi. Część I - Karolina Królewska; Joanna Saluk-Juszczak (Menopause Review, 2010)
The main function of blood platelets is their haemostatic role, but recent evidence shows that processes of platelet activation may be sometimes a critical link between haemostasis and development of inflammation. In many pathological processes related to cardiovascular disorders, e.g. changes connected with menopause, enhanced platelet activation is observed in atherosclerosis, diabetes and cancer, in which proinflammatory and prothrombotic CD40/CD40L pathway is involved. Platelets are responding to a large number of physiologically important compounds because they possess a number of specific membrane receptors. The biological activity substances secreted from activated platelets are important factors of inflammatory reactions and increase platelet interaction with immunological cells. The inhibition of CD40/CD40L pathway, involved in blood platelet activation in many pathological processes, may provide an alternative treatment for various diseases in the future.